A Virtual Escape Room Plot to Enhance Undergraduate Dental Students’ Skills in Radiographic Differential Diagnosis - Fatma Fayez Badr; Hanadi M. Khalifa (Journal of International Clinical Dental Research Organization)
Background/Objectives: The use of gamification – game concepts and elements applied in nongame contexts – has garnered considerable interest across various sectors, including healthcare and education. This study aims to showcase the effectiveness of a virtual escape room (vER) activity to enhance undergraduate dental student’s understanding of differential diagnosis in oral through interactive and challenging cases. In addition, the study explores how this approach may influence student knowledge, identifies potential benefits, and highlights relevant challenges for implementing such gamification strategies in oral radiology education. Materials and Methods: The vER was created using Google Forms to engage dental students as part of the undergraduate oral radiology course. Following the initial formal presentation about the topic, this Es-R activity took place 1 week after in a classroom setting, engaging a total of 80 students. Knowledge was assessed using a pre and postactivity questionnaire. Feedback was collected using the Likert scale. A paired-sample t-test was used to analyze the difference between the preactivity and postactivity scores, and statistical significance was assessed at P < 0.05. Results: A significant increase in scores was noted from preactivity to postactivity. The mean preactivity score was 6.19 (standard deviation [SD] =1.8), whereas the mean postactivity score was 8.95 (SD = 1.2) out of 10 maximum points. A paired sample t-test revealed that the increase in scores was statistically significant (P < 0.001). Conclusions: The findings of this study suggest that the vER activity significantly enhanced student knowledge, with overall positive feedback from participants. These findings suggest that such gamification strategies can boost academic performance. Further research is recommended to explore long-term retention of knowledge gained through such methods.